Landscaping for road traffic noise abatement: Model validation. (November 2018) - Van Renterghem, Timothy; Botteldooren, Dick
Abstract: Deliberately changing terrain undulation and ground characteristics ("acoustical landscaping") is an potential noise abatement solution near roads. However, there is hardly any research regarding the validity of sound propagation models to predict its effectiveness. Long-term continuous sound pressure level measurements near a complex road traffic and sound propagation case were performed. Three types of modeling approaches were validated, covering the full spectrum of available techniques. A two-dimensional full-wave technique (the finite-difference time-domain method, FDTD), but also an advanced engineering model (the Harmonoise point-to-point model), provide accurate transmission loss predictions, both in 1/3 octave bands and for total A-weighted sound pressure levels. Two common and widely used semi-empirical engineering methods (ISO9613-2 and CNOSSOS) yield rather inaccurate results, notwithstanding the short propagation distance. The sensitivity to input data was assessed by modeling various scenarios with the FDTD method. Detailed ground effect modeling was shown to be of main importance. Highlights: The idea of "acoustical landscaping" has been introduced. Combined terrain undulation and ground type can abate road traffic noise efficiently. Full-wave and diffraction based models accurately predict sound transmission losses. Common engineering methods provide only poor predictions even at short range. Detailed ground property modeling is of main importance near natural embankments.